2009
DOI: 10.1103/physrevlett.103.255701
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Analysis of Random Networks with Explosive Percolation

Abstract: The existence of explosive phase transitions in random (Erdős Rényi-type) networks has been recently documented by Achlioptas et al. [Science 323, 1453[Science 323, (2009] via simulations. In this Letter we describe the underlying mechanism behind these first-order phase transitions and develop tools that allow us to identify (and predict) when a random network will exhibit an explosive transition. Several interesting new models displaying explosive transitions are also presented. PACS numbers: Valid PACS ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
180
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(189 citation statements)
references
References 15 publications
9
180
0
Order By: Relevance
“…This growth rule, named as the Achlioptas process (AP), is then studied on the two-dimensional lattice [2,3] and on the scalefree networks [4][5][6] as well, yielding similar results. That suddenness has been widely believed to indicate a discontinuity at the percolation transition in the thermodynamic limit [7,8], and the similar explosiveness has been observed with the other growth rules proposed later [9][10][11][12][13]. These observations of the explosiveness have drawn much interest due to the striking difference from the wellknown continuous transition in the standard percolation models [14].…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…This growth rule, named as the Achlioptas process (AP), is then studied on the two-dimensional lattice [2,3] and on the scalefree networks [4][5][6] as well, yielding similar results. That suddenness has been widely believed to indicate a discontinuity at the percolation transition in the thermodynamic limit [7,8], and the similar explosiveness has been observed with the other growth rules proposed later [9][10][11][12][13]. These observations of the explosiveness have drawn much interest due to the striking difference from the wellknown continuous transition in the standard percolation models [14].…”
mentioning
confidence: 53%
“…These observations of the explosiveness have drawn much interest due to the striking difference from the wellknown continuous transition in the standard percolation models [14]. However, in our point of view, the explosiveness has not been carefully investigated as yet enough to draw a decisive conclusion on the discontinuity, and possibly just represents an extremely steep but still continuous transition.Friedman and Landsberg [9] have suggested the argument of the powder keg as a circumstantial description to explain the apparent discontinuity of the explosive percolation transition. Meanwhile, da Costa et al [15] have reported that the explosive percolation is actually continuous for a modified version of the AP by analytically deriving the critical scaling relations based on numerical observations of power-law critical distribution of cluster size [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These jumps are discontinuous phase transitions. However, when such mechanisms are mixed, even weakly, with mechanisms that merge components purely at random then the transitions vanish, or become at most weakly discontinuous characterized by very small power law exponents [30][31][32][33][34][35][36][37][38][39][40][41] , see Supplementary Methods and Supplementary Figs S1-S3.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Achlioptas et al [39] studied percolation for the Erdos Renyi model using a product rule and found that the giant component emerged suddenly at the percolation threshold, and that the percolation transition was discontinuous. This discontinuous percolation transition appears when the growth of the largest cluster is systematically suppressed thereby promoting the formation of several large components that eventually merge in an explosive way [40]. Several aggregation models, based on percolation, have been developed to achieve this change in the nature of transition [19,39,[41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%